1991
DOI: 10.1111/j.1365-2621.1991.tb04762.x
|View full text |Cite
|
Sign up to set email alerts
|

Texture and Microstructure of Cassava (Manihot esculenta Crantz) Flour Extrudate

Abstract: Cassava flour (Man&r esculenta Crantz) was texturized by singlescrew extrusion processing. Relationships between texture and microstructure as a function of extrusion variables were examined. The effect of feed moisture or screw speed was significant (P < 0.01) on all textural parameters except springiness and energy first bite. Hardness, gumminess (P < 0.05) fracturability and cohesiveness (P < 0.01) decreased with increasing temperature. Hardness, fracturability and firmness were lowest at screw speed 520 rp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 2 publications
7
19
0
2
Order By: Relevance
“…Extrusion temperature and moisture content are known to affect gelatinization during extrusion, and consequently the WAI. In high moisture soy meat analog, WAI increased with increase in extrusion temperature and feed moisture [38,39]. Similar results were reported for corn starch extrudates, bean and chickpea extrudates [40,41].…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)supporting
confidence: 76%
“…Extrusion temperature and moisture content are known to affect gelatinization during extrusion, and consequently the WAI. In high moisture soy meat analog, WAI increased with increase in extrusion temperature and feed moisture [38,39]. Similar results were reported for corn starch extrudates, bean and chickpea extrudates [40,41].…”
Section: Water Absorption Index (Wai) and Water Solubility Index (Wsi)supporting
confidence: 76%
“…Increasing feed moisture content significantly increased hardness of the extrudate. Previous studies have also reported that hardness of extrudate increased as the feed moisture content increased (Badrie and Mellowes 1991;Liu et al 2000). Extrusion process parameter such as screw speed was found to have no significant effect on extrudate hardness.…”
Section: Texturementioning
confidence: 73%
“…It would be expected that high density and low expansion would produce a harder extrudate. Previous studies also reported that the hardness of extrudate increased as the feed moisture content increased (Badrie & Mellowes, 1991;Liu, Hsieh, Heymann, & Huff, 2000). Liu et al (2000) suggested that reduced expansion could be caused by the increase in moisture content.…”
Section: Textural Analysismentioning
confidence: 90%